Multifactorial in vivo regulation of the photoreceptor channelrhodopsin-1 abundance. - Wolfram, Michaela; Greif, Arne; Sizova, Irina; Baidukova, Olga; Hegemann, Peter; Kreimer, Georg (Plant Cell and Environment, 2023)
Oriented movement (phototaxis) is an efficient way to optimize light-driven processes and to avoid photodamage for motile algae. In Chlamydomonas the receptors for phototaxis are the channelrhodopsins ChR1 and ChR2. Both are directly light-gated, plasma membrane-localized cation channels. To optimally adjust its overall light-dependent responses, Chlamydomonas must tightly control the ChRs cellular abundance and integrate their activities into its general photoprotective network. How this is achieved is largely unknown. Here we show that the ChR1 protein level decreases upon illumination in a light-intensity and quality-dependent manner, whereas it is stable in prolonged darkness. Analysis of knockout strains of six major photoreceptors absorbing in the blue-violet range, which is most effective in evoking ChR1 degradation, revealed that only phototropin (PHOT) is involved. Notably, ChR2 degradation was normal in a ΔPHOT strain. Further, our results indicate that a COP1-SPA1 E3 ubiquitin ligase, the transcription factor Hy5 as well as changes in the cellular redox poise and cyclic nucleotide levels are additional components involved in this light acclimation response of Chlamydomonas. Our data highlight the presence of an adaptive framework connecting phototaxis with general photoprotective mechanisms via the use of overlapping signaling components already at the level of the primary photoreceptor.